ENTREPRENEURIAL LEGAL PERSONALITY OF A JUVENILE ENTREPRENEUR - G. V. Stankevich (Гуманитарные и юридические исследования)
The article analyzes the features of the entrepreneurial legal personality of juvenile entrepreneurs and the mechanism of its formation and implementation. The author makes a proposal to indicate in the registration certificate of an entrepreneur that the person is under age. The author analyses particular features of the protection of the legal capacity of juvenile entrepreneurs in business activities.